Cross-sectional Study Reveals Moderate Professional Benefits Among Nurses in a Multicultural Healthcare System - Ka Ieng Lai MSc; Pedro Fong PhD; Lirong Meng PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The global nursing shortage poses challenges to healthcare accessibility, clinical outcomes, and patient safety. Researchers have explored factors that influence nursing attrition, and the Nurses’ Perceived Professional Benefits (NPPB) is one such factor that has gained attention. This cross-sectional study aims to assess the NPPB among registered nurses in Macao, a multicultural city with a unique healthcare system. A 33-item online questionnaire was used to collect data from 279 nurses. The questionnaire measured NPPB across 5 dimensions: positive occupational perception, personal enhancement, recognition from family and friends, decent nurse-patient relationships, and team belongingness. This study indicated that Macao nurses had a moderate level of NPPB. Nurse-patient relationships, income, and job stability received the most positive responses, while team belongingness received the lowest scores. These findings suggest that improvements are needed in team building, providing more opportunities for specialized training, and offering more career advancement opportunities.